2019
DOI: 10.1161/jaha.119.012205
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Meteorological Factors and the Rupture of Intracranial Aneurysms

Abstract: BackgroundBoth meteorological factors and morphological factors are important factors to predict intracranial aneurysm rupture. This study investigated the relationship between meteorological factors and aneurysmal subarachnoid hemorrhage (aSAH). Additionally, the morphological differences between ruptured and unruptured aneurysms under these high‐risk meteorological conditions were assessed.Methods and ResultsThe records of 1751 patients with aSAH with 2124 intracranial aneurysms were retrospectively analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
8
1
3
Order By: Relevance
“…The incidence of aSAH is higher in winter and January/December compared to that in summer and July. Previous clinical studies reported similar results [ 5 11 15 16 17 ]. This circannual pattern could be associated with ambient temperature.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The incidence of aSAH is higher in winter and January/December compared to that in summer and July. Previous clinical studies reported similar results [ 5 11 15 16 17 ]. This circannual pattern could be associated with ambient temperature.…”
Section: Discussionsupporting
confidence: 75%
“…This circannual pattern could be associated with ambient temperature. Low daily mean, maximum, and minimum temperatures were associated with an increased rate of aSAH [ 11 ]. Another research also reported that temperature decline from the previous day is a trigger for the occurrence of aSAH [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on factors that contribute to an increased risk of rupture of IAs have mainly focused on morphological factors and primary diseases (5,6). Recently, hemodynamic factors, such as the oscillatory shear index, wall shear stress, and blood flow velocity, have been shown to be associated with the formation, progression, and rupture of IAs (7,8). Wall shear stress is regarded as the most important factor for IA initiation and rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between morphological factors and the rupture rate of IAs has become a research hot spot. Although many studies have evaluated the relationship between geometric features and IA rupture, there are still great differences (8)(9)(10). In addition, genetic factors have been shown to be closely associated with ruptured IAs, and significant efforts have sought to identify genetic biomarkers for IA rupture (11).…”
Section: Introductionmentioning
confidence: 99%